Storage Stability of Chilled and Frozen Starch Gels as Affected by Blended Starch Formulation, Sucrose Syrup, and Coconut Milk - Aumaporn Arlai; Kanitha Tananuwong (International Journal of Food Science)
Effects of starch formulation, highly concentrated sucrose solution, and coconut milk on the stability of starch gels kept under chilled and frozen conditions were determined. Gels containing rice starch (RS), tapioca starch (TS) (RS:TS of 1 : 0.85), and hydroxypropyl distarch phosphate (HDP, 0-50% of total starch) were prepared from 15% starch suspension using water, 45°Brix sucrose syrup or coconut milk as liquid media. After aging at 4°C for 21 days, starch gels had higher hardness and chewiness, with lower cohesiveness and springiness (p≤0.05). Water-based gels containing HDP had less extent of texture hardening, lower degree of crystallinity, and more homogeneous microstructure during 4°C aging. However, for the starch gels in sucrose syrup or coconut milk, HDP induced greater gel hardening, higher degree of crystallinity, and denser gel microstructure during chilled storage. This could be due to the crystallization of sucrose or lipid/amylose-lipid complexes. Nevertheless, HDP enhanced freeze-thaw stability of the gels, regardless of the liquid media used (p≤0.05). According to the consumer test of the model desserts subjected to a single freeze-thaw cycle, the sample containing 50% HDP gel in sucrose syrup or 25% HDP gel in coconut milk gained the highest hedonic score of texture and overall acceptance (p≤0.05).